On physical exercise in the article “Update on the neurophysiology of sexual behavior and reproductive risk in adolescents” - Cortés Cortés, Manuel Enrique (Revista Habanera de Ciencias Médicas, 2025)
Dear Editor, The interesting article by Salgado et al.,(1) published in the Revista Habanera de Ciencias Médicas, offers a comprehensive review of the neurophysiology of sexual behaviour in adolescents, highlighting factors that influence decision-making and reproductive risk. Within this context, the purpose of this Letter to the Editor is to contribute to the discussion by addressing the impact of physical exercise on adolescents’ neurocognitive and emotional development, given its potential as a modulating factor in behavioural regulation and the prevention of impulsivity-related risks.